Makna Simbolik Arsitektur Rumah Adat Limbungan: Studi Etnografi di Desa Perigi Lombok Timur - Novi Ayu Ningsih; Abdul Rasyad; Muhammad Shulhan Hadi (Universitas Hamzanwadi, 2024)
This study aims to reveal the symbolic meaning of the Limbungan traditional house architecture in Perigi Village, Suela, East Lombok and its historical development. The research employs a qualitative approach with ethnographic methods. Data collection was conducted through observation, in-depth interviews with customary leaders, traditional figures, and community leaders, as well as documentation. Data analysis techniques use ethnographic methods to systematically study human culture. The results show that the Limbungan traditional house has deep cultural significance and has existed since the colonial era. These traditional houses not only function as dwellings but also as symbols of Limbungan community identity. The construction uses natural materials such as earth, bamboo, wood, and thatch. The Limbungan traditional house follows the traditional Sasak architectural structure consisting of bale (house) and panteq (barn) that face each other in pairs. House components include atep bale (roof), julu lawang (yard), pager (wall), lawang (door), and undak-undak (stairs), each carrying symbolic meanings that reflect cultural values, beliefs, and local wisdom of the Sasak Limbungan community. This research contributes to cultural heritage preservation and understanding of Nusantara traditional architecture.